Synthesis, characterization and antimicrobial activity of new Cu(II) and Zn(II) complexes with Schiff bases derived from trimethylsilyl-propyl-p-aminobenzoate. (4th November 2015) - Zaltariov, Mirela-Fernanda; Cazacu, Maria; Avadanei, Mihaela; Shova, Sergiu; Balan, Mihaela; Vornicu, Nicoleta; Vlad, Angelica; Dobrov, Anatolie; Varganici, Cristian-Dragos
Graphical abstract: A Cu(II) and two Zn(II) complexes of the Schiff bases derived from an original amine, trimethylsilyl-propyl- p -aminobenzoate, reacted with salicylaldehyde and o -vanillin were obtained. These proved to be fluorescent, having green emission, and biologically active. Abstract: Three mononuclear complexes, one of Cu(II) {[Cu(L A )2 ] (4 )}, and two of Zn(II) {[Zn(L A )2 ] (5 ) and[Zn(L B )2 (H2 O)2 ] 2+ (6 )} have been synthesized through treating the corresponding metal salts with Schiff bases of trimethylsilyl-propyl- p -aminobenzoate with salicylaldehydeHL A (2) and o -vanillinHL B (3) . The Schiff base ligands and their metal complexes were structurally confirmed by spectral techniques (FTIR, 1 H NMR, 13 C NMR, ESI-MS, elemental analysis) and single crystal X-ray diffraction. Crystallographic data revealed different coordination environments of the metal ions: a strict square-planar geometry of the copper ion in4, a distorted tetrahedral geometry of the zinc ion in5, and an usual (O6 ) octahedral coordination of the zinc ion in6 . Spectral analysis of optical emission indicated that Zn(II) complexes exhibit strong fluorescence properties as compared with the ligands and Cu(II) complex. Thermogravimetric analysis results suggested a lower stability of the metal complexes in comparison with the free ligands. The antifungal and antibacterial properties of the prepared compounds against Aspergillus fumigatus ATCC 66567, Penicillium chrysogenum ATCC 20044, Fusarium ATCC 20327, Bacillus sp . ATCC 31073, Pseudomonas sp . ATCC 15780 were evaluated. Both Schiff bases and metal complexes showed better antimicrobial activity compared to the standard compounds Caspofungin and Kanamycin.